2010
DOI: 10.1007/s00705-010-0779-9
|View full text |Cite
|
Sign up to set email alerts
|

Anti-herpes simplex virus effects of berberine from Coptidis rhizoma, a major component of a Chinese herbal medicine, Ching-Wei-San

Abstract: Berberine is an alkaloid extracted from Coptidis rhizome. Among the individual herbal components of a Chinese herb medicine, Ching-Wei-San, Coptidis Rhizoma has the most potent antimicrobial activity. By high-pressure liquid chromatography, the quantitative analysis of berberine from 6.25-mg/mL (w/v) Coptidis rhizome extract or 50.00-mg/mL (w/v) Ching-Wei-San was determined to be 0.26 mg/mL. To explore the potential use of Ching-Wei-San against herpes simplex virus (HSV) infection, the cytotoxicity, anti-HSV-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 26 publications
0
44
0
Order By: Relevance
“…Berberine is an alkaloid extracted from Chinese herbal plant Coptidis rhizome and demonstrated in‐vitro antiherpetic activity with IC50 values for HSV‐1 and HSV‐2 24.4 and 26.8 μ m , respectively. Moreover, its mechanism of action is due to the prevention of penetration of virus into the cell [82]. Another alkaloid FK‐3000 was obtained from the methanolic extract of Stephania cepharantha and showed in‐vivo anti‐HSV‐1 activity.…”
Section: Pure Compounds and Fractions That Possess Anti‐hsv Activitiesmentioning
confidence: 99%
“…Berberine is an alkaloid extracted from Chinese herbal plant Coptidis rhizome and demonstrated in‐vitro antiherpetic activity with IC50 values for HSV‐1 and HSV‐2 24.4 and 26.8 μ m , respectively. Moreover, its mechanism of action is due to the prevention of penetration of virus into the cell [82]. Another alkaloid FK‐3000 was obtained from the methanolic extract of Stephania cepharantha and showed in‐vivo anti‐HSV‐1 activity.…”
Section: Pure Compounds and Fractions That Possess Anti‐hsv Activitiesmentioning
confidence: 99%
“…Berberine has been shown to inhibit the growth of certain tumor-derived cell lines [16][17][18][19][20] and to prevent the growth of certain bacteria [21][22][23][24][25][26]. Berberine can effectively inhibit the growth of several viruses [27][28][29] including human cytomegalovirus and herpes simplex virus. Berberine has also been shown to inhibit production of cytokines, inflammatory lipids, and nitric oxide from macrophages treated with LPS [3,30].…”
Section: Introductionmentioning
confidence: 99%
“…Chin et al first reported that berberine from Coptidis rhizoma showed an anti-HSV effect (41). Due to its low cytotoxicity and minimal side effects, berberine is considered a promising antiviral drug candidate for alternative treatment.…”
Section: Discussionmentioning
confidence: 99%